Classement des sols selon leurs possibilités d’utilisation agricole - Mailloux, Auguste; Dubé, Armand; Tardif, Lauréan (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1964)
This paper presents a binary soil capability classification System which bas been developed and used in Québec since 1958.The system bas been designed to provide some basic and essential information, regarding the value of the soil, to be integrated in a broad agricultural and economic survey of the region.The basic criteria of the present system are : 1. the fundamental value of the soil determined by the characteristics of the soil profile ; and, 2. the kind and importance of management practices required, v.g. : correction of unfavourable internal or external limitations ; or, indications for a restricted use of the land such as : permanent pasture, wildlife, recreation and forestry.In this system, the capability class is derived by integrating these two variables ; or, in other words, the class is the result of the combination of these two fundamental criteria. The close relation between these two factors or parameters is ex-pressed in the scheme presented in tables I and II for mineral and organic soils respectively.This logical and practical method seems suitable and adaptable to describe any set of landscapes which are of interest to agronomists, economists and regional planning commissions. The regions of Bas-Saint-Laurent, Gaspésie, Iles-de-la-Madeleine and Montréal have been mapped according to this system.